Community perceptions of the agricultural impacts of Myanmar’s health and political crises: Insights from the National COVID 19 Community Survey – September 2021 - Myanmar Agriculture Support Activity (International Food Policy Research Institute, 2021)
Key findings Forty-two percent of farming communities experienced lower agricultural production than normal in the past 12 months, mainly due to drought and pests. Forty-four percent of farming communities reported greater difficulties in selling agricultural products than usual. Low crop price was the most frequently reported disruption. There are pressing concerns for the upcoming monsoon season harvest. Inorganic fertilizer prices are skyrocketing–compound fertilizer prices increased 56 percent in September 2021 compared to September 2020 while urea prices increased 72 percent compared to last year. About one-third of farming communities hired fewer agricultural wage workers this year compared to last year, with 46 percent reporting that this was mainly due to financial problems. For the current monsoon season, 45 percent of farming communities expect overall agricultural production will be lower than that of last year. Recommended actions Implement measures such as input subsidies, vouchers, or agricultural grants to limit the impact of the price increases of fertilizers and other inputs on agricultural production. As farming communities risk falling into vicious cycles of income loss, financial support is urgently needed to avoid long-lasting impacts of the crises on the agricultural performance of affected communities. Social protection is urgently needed in rural areas, including food/cash for work schemes to offset lower demand for agricultural labor.